Establishment of a Mouse Ovarian Cancer and Peritoneal Metastasis Model to Study Intraperitoneal Chemotherapy - Rezniczek, Günther A. (Cancers (Basel), 2020)
SIMPLE SUMMARY: Intraperitoneal chemotherapy (IPC) is a locoregional treatment option in patients with peritoneal metastases (PM). Small animal models are valuable research tools allowing for rapid, reproducible, and inexpensive study and optimization of different forms of IPC. Here, we present a mouse model of ovarian cancer-derived PM and demonstrate its suitability for various modes of IPC, including pressurized intraperitoneal chemotherapy (PIPAC) using a micro-nozzle for aerosolized drug delivery. ABSTRACT: Intraperitoneal chemotherapy (IPC) is a locoregional treatment option in patients with peritoneal metastases (PM). Here, we present an ovarian cancer (OC)-derived PM mouse model for the study of different forms of IPC. Xenograft cell proliferation (luciferase-transfected OVCAR3 and SKOV3 clones) and growth kinetics were assessed using PET scan, bioluminescence imaging (BLI), and histological tumor analysis. Liquid IPC was achieved by intraperitoneal injection with/without capnoperitoneum (6–7 mmHg). Pressurized intraperitoneal aerosol chemotherapy (PIPAC) was mimicked using an intratracheal drug aerosol administration system (micro-nozzle), which, as demonstrated by ex vivo granulometric analysis using laser diffraction spectrometry, produced a polydisperse, bimodal aerosol with a volume-weighted median diameter of (26.49 ± 2.76) µm. Distribution of Tc-99m-labeled doxorubicin in mice was characterized using SPECT and was dependent on the delivery mode and most homogeneous when the micro-nozzle was used. A total of 2 mg doxorubicin per kg body weight was determined to be the optimally effective and tolerable dose to achieve at least 50% tumor reduction. Repeated PIPAC (four times at seven-day-intervals) with doxorubicin in SKOV3-luc tumor-bearing mice resulted in halted tumor proliferation and tumor load reduced after the second round of PIPAC versus controls and the number of tumor nodules was significantly reduced (27.7 ± 9.5 vs. 57.3 ± 9.5; p = 0.0003). Thus, we established the first mouse model of OC PM for the study of IPC using a human xenograft with SKOV3 cells and an experimental IPC setup with a miniaturized nozzle. Repeated IPC was feasible and demonstrated time-dependent anti-tumor activity.